Pengaruh Penggunaan E-Wallet dan Shopping Behavior terhadap Perilaku Impulse Buying Generasi Z di Bandar Lampung dengan Self Control sebagai Variabel Moderasi: Perspektif Kewirausahaan - Cinthya Bella; Maharani, Nabila Putri; Melisa Alivia (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The purpose of this study is to identify and examine the influence of e-wallet usage and shopping lifestyle on the impulse buying behavior of Generation Z in Bandar Lampung, as well as to test the role of self-control as a moderating variable. This study uses a quantitative method. The population in this study consists of all Generation Z in Bandar Lampung City who use e-wallets, and the total number is unknown. The sample used in this study consists of 170 respondents. The data source used in this study is primary data obtained through the distribution of questionnaires. The data analysis technique in this study uses Partial Least Square (PLS) with the help of the SmartPLS application. The results of this study indicate that e-wallet usage and shopping lifestyle have a positive and significant effect on impulse buying behavior. In addition, self-control moderates the influence of e-wallet usage on impulse buying behavior in a negative direction, while self-control moderates the influence of shopping lifestyle on impulse buying behavior in a positive direction.